Pengaruh Mekanisme Corporate Governance Terhadap Tingkat Kepatuhan Mandatory Disclosure Pasca Konvergensi IFRS - Isna Fauziah (Esensi: Jurnal Bisnis dan Manajemen, 2015)
The proportion of independent commissioners and the number of audit committee meeting. Data analysis method used is descriptive analysis method and hypothesis testing. The result in this study showed the average level of mandatory disclosure compliance after convergence of IFRS in statement comprehensive income is 59.73%. The result showed that corporate governance mechanism simultaneously affect the level of compliance with mandatory disclosure after convergence of IFRS. Meanwhile corporate governance mechanism variables that affect compliance are the managerial ownership, institutional ownership and the proportion of independent commissioners. Other variable that no affect is the numbers of audit committee meeting.DOI: 10.15408/ess.v5i2.2349